Experimental investigation on tribological properties of UHMWPE with the addition of basalt fiber. (12th December 2019) - Han, Yi; Chen, Jihong
To seek the effective and feasible way to enhance the tribological properties of ultrahigh-molecular-weight polyethylene (UHMWPE) materials, a comparative investigation on the tribological behavior of basalt fiber (BF) as filler in UHMWPE composites was carried out. BF/UHMWPE composites were investigated through friction and wear tests to evaluate its frictional and lubricate properties. The results showed that the friction coefficient of the UHMWPE composite decreased significantly under water sliding condition; under water and dry friction conditions, the friction coefficient decreases with the increase in load and rises as the rotational speed growing. When the BF/UHMWPE composites were tested under water-lubricated conditions, the material folding and pieces of debris were reduced obviously and the variation of wear depth was consistent with the results of friction coefficient. To evaluate the tribological properties of UHMWPE under various conditions, the research results make useful reference for UHMWPE manufacture and other relative experiments.